REPRESENTATION OF PSYCHOLOGICAL TERMS IN DICTIONARIES - Guzal Qurbonaliyevna Ergasheva (Bright Mind Publishing, 2025)
This article discusses the history of the development of psychology, its various definitions throughout different periods, and modern psychological concepts. It highlights that psychology was initially not recognized as an independent discipline but was considered part of philosophy. Additionally, the article examines the formation of psychological terminology in Russian and Uzbek languages, the role of terminological dictionaries, and their significance in the advancement of psychology. Special attention is given to psychological dictionaries and encyclopedias published in Russian, which have highlighted the necessity of developing new terminological sources in the Uzbek language. The article provides a detailed analysis of the diversity of existing psychological terms in Uzbek and the importance of their scientific foundation.
Keywords: Psychology, psychological terminology, dictionaries, encyclopedia, psychological concepts, scientific research, Uzbek and Russian languages, scientific development, pedagogy, terminology formation.